EpCAM and microvascular obstruction in patients with STEMI: a cardiac magnetic resonance study. (13th July 2021) - Rios-Navarro, C; Gavara, J; Nunez, J; Bonanad Lozano, C; Revuelta-Lopez, E; Monmeneu, JV; Lopez-Lereu, MP; De Dios, E; Perez-Sole, N; Vila, JM; Oltra, R; Chorro, FJ; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This study was funded by "Instituto de Salud Carlos III" and "Fondos Europeos de Desarrollo Regional FEDER" Bachground. Microvascular obstruction (MVO) is negatively associated with cardiac structure and worse prognosis after ST-segment elevation myocardial infarction (STEMI). Epithelial cell adhesion molecule (EpCAM), involved in endothelium adhesion, is an understudied area in the MVO setting. Purpose. We aimed to evaluate whether EpCAM is associated with the appearance of cardiac magnetic resonance (CMR)-derived MVO and long-term systolic function in reperfused STEMI. Methods. We prospectively included 106 patients with a first STEMI treated with primary percutaneous coronary intervention, quantifying serum levels of EpCAM 24 hours post-reperfusion. All patients underwent CMR imaging 1 week and 6 months post-STEMI. The independent correlation of EpCAM with MVO, systolic volume indices, and left ventricular ejection fraction (LVEF) was evaluated. Results. The mean age of the sample was 59 ± 13 years and 76% were male. Patients were dichotomized according to EpCAM median (4.48 pg/mL). At 1-week CMR, lower EpCAM was related to extensive MVO (p-value = 0.02) and greater infarct size (p-value = 0.02). At presentation, only EpCAM values were significantly associated with the presence of MVO in univariate (Odds Ratio [95% confidence interval] (OR [95% CI]): 0.58 [0.38-0.88], p-value = 0.01) and multivariate logistic regression models (OR [95% CI]: 0.54 [0.34-0.85], p-value = 0.007). Although MVO tends to resolve at chronic phases, decreased EpCAM was associated with worse systolic function: depressed LVEF (p-value = 0.009) and higher left ventricular end-systolic volume (p-value = 0.04). Conclusions. EpCAM is associated with occurrence of CMR-derived MVO at acute phases and long-term adverse ventricular remodeling post-STEMI. Future studies are needed to confirm EpCAM as biomarker, and eventually biotarget in STEMI pathophysiology.